Adaptations of Prefrontal Brain Activity, Executive Functions, and Gait in Healthy Elderly Following Exergame and Balance Training: A Randomized-Controlled Study - Schättin, Alexandra; Arner, Rendel; Gennaro, Federico; de Bruin, Eling D. (Frontiers in Aging Neuroscience, 2016)
During aging, the prefrontal cortex (PFC) undergoes age-dependent neuronal changes influencing cognitive and motor functions. Motor-learning interventions are hypothesized to ameliorate motor and cognitive deficits in older adults. Especially, video game-based physical exercise might have the potential to train motor in combination with cognitive abilities in older adults. The aim of this study was to compare conventional balance training with video game-based physical exercise, a so-called exergame, on the relative power (RP) of electroencephalographic (EEG) frequencies over the PFC, executive function (EF), and gait performance. Twenty-seven participants (mean age 79.2 ± 7.3 years) were randomly assigned to one of two groups. All participants completed 24 trainings including three times a 30min session/week. The EEG measurements showed that theta RP significantly decreased in favor of the exergame group (L(14) = 6.23, p = 0.007). Comparing pre- vs. post-test, EFs improved both within the exergame (working memory: z = -2.28, p = 0.021; divided attention auditory: z = -2.51, p = 0.009; divided attention visual: z = -2.06, p = 0.040; go/no-go: z = -2.55, p = 0.008; set-shifting: z = -2.90, p = 0.002) and within the balance group (set-shifting: z = -2.04, p = 0.042). Moreover, spatio-temporal gait parameters primarily improved within the exergame group under dual-task conditions (speed normal walking: z = -2.90, p = 0.002; speed fast walking: z = -2.97, p = 0.001; cadence normal walking: z = -2.97, p = 0.001; stride length fast walking: z = -2.69, p = 0.005) and within the balance group under single-task conditions (speed normal walking: z = -2.54, p = 0.009; speed fast walking: z = -1.98, p = 0.049; cadence normal walking: z = -2.79, p = 0.003). These results indicate that exergame training as well as balance training positively influence prefrontal cortex activity and/or function in varying proportion.